Pathological Skin Picking: Phenomenology and Associations With Emotions, Self-Esteem, Body Image, and Subjective Physical Well-Being - Gallinat, Christina; Stürmlinger, Linda Luisa; Schaber, Sandra; Bauer, Stephanie (Frontiers in Psychiatry, 2021)
Pathological skin picking (PSP) refers to the repetitive manipulation of the skin causing wounds, scars, emotional distress and social impairment. Skin picking disorder was first recognized as a distinct disorder in the DSM-5 and is still understudied in terms of phenomenology, etiology, and associated consequences. However, the body-related pathology suggests that the relation to the own body might be a crucial factor in PSP. Previous studies provided first insights that affected individuals show a more negative body image and lower self-esteem than healthy individuals. The present study sought to investigate skin picking phenomenology, related emotions as well associations with self-esteem, body image and subjective physical well-being. The study was conducted as an open online study, and recruitment was generally targeted to individuals of full age and in addition specifically to individuals with PSP. A total of 363 individuals (82.9% female; age: M=32.6, SD=13.92) participated and answered various self-report measures. Nearly half of the sample exceeded the cutoff score for pathological skin picking (N=163; 44.9%). The results suggest that boredom, bodily tension and strong negative feelings often precede PSP episodes. During the episode most individuals seem to experience a loss of control, trance and positive feelings. After the PSP episode, shame, guilt, anger and anger towards themselves are most prominent. As expected, skin picking severity was positively associated with body image disturbances and negatively with self-esteem, and subjective physical well-being. When controlling for depressive symptoms, all associations were reduced, but those with body-image disturbances (r=.44; p<.001), self-esteem (r=-.27; p<.001), subjective physical well-being (r=-.22; p<.001) and peace of mind (r=.30; p<.01) remained significant. Moreover, greater skin damage due to skin picking was moderately associated with higher body image disturbances. The results indicate that PSP severity is associated with a negative body image and low self-esteem, and suggest that it may be warranted to consider these aspects in the development of future interventions for PSP. However, relations with body image and self-esteem should be examined in longitudinal studies investigating causal relationships between body image, self-esteem and skin picking. Moreover, PSP phenomenology and the role of specific emotions should be investigated in more detail.